Comparison of signature on paper and apple® ipad using multivariate analysis - Xian, Lim Sue (2022)
The transformation of documentation either in legal public or private industry had moved with the digitalization of business around the world in an unpredicted acceleration in last two decades particularly since the Covid-19 pandemic. The Forensic Document Examiners (FDEs) for this study was on high demand to move forward toward digital document examination just like the way they did for conventional physical document examination. Signature, being one of the most socially acceptable biometric traits for the past centuries, has become one of the challenges when a handwritten signature was digitally captured on digital device instead of the traditional paper as writing medium. Most of the previously available research focused on the temporal digital data for the features and characteristics of handwritten signatures. This study aimed to focus on the height ratio analysis of writing zones in handwritten signatures deposited on paper medium and on the Apple® iPad medium when both were treated as static flat images when the digital document was not made available to the FDE. The results indicated that there were differences for signatures on different writing mediums as opposed to the principle of handwriting that the writing zone of a person remained relatively uniform in most of the aspects. The implementation of statistical approaches allowed the handwriting examination being presented in quantitative and objective opinions to the court of law by using